The effect of silicon dioxide on knee Osteoarthritis: A randomized clinical trial - Amir Davoodabadi Farahani; Maryam Hassaninevisi; Ali Sobhani Firoozabadi; Seyed Mohamad Hosseinian; Fatemeh Shirani (Acta Medica Iranica, 2023)
Osteoarthritis (OA) is the most common type of arthritis and although there is no definitive cure for it, there are treatments for symptom management. The present study was conducted to evaluate the effects of silicon dioxide (SiO2) on clinical symptoms of knee OA and compare it with avocado soybean unsaponifiable (ASU) and placebo. This study is a double-blind randomized clinical trial on 104 patients with knee OA referred to Rheumatology Clinic, Rasoul Akram Hospital, Tehran. Patients were randomly divided into three groups, including patients treated with ASU, SiO2, and placebo for 3 months. Subsequent referral was performed at weeks 4, 8, and 12, and the stiffness, physical function, and pain scores were recorded based on the WOMAC questionnaire. In this study, the effect of treatment of placebo and SiO2 and ASU in patients with knee OA based on WOMAC questionnaire showed a significant reduction in terms of pain, joint stiffness, physical function, and total scores of WOMAC in the cases of the SiO2 group compared with the other two groups. The findings of this study showed that the therapeutic effects of SiO2 in patients with knee OA in terms of pain and stiffness and physical function scores were more than the ASU and placebo groups.